Recurrent miscarriage and infertility: a national service evaluation - Laura Linehan; Marita Hennessy; Keelin O’Donoghue (Journal of Obstetrics and Gynaecology, 2023)
The appropriate clinical care of women/couples with infertility experiencing recurrent miscarriage (RM) is overlooked in international guidelines. We sought to evaluate care provision for women/couples with RM and infertility across public (19 clinics providing RM care, five fertility clinics) and private sectors (nine fertility clinics) using adapted guideline-based key performance indicators (KPIs) for RM. An online survey comprised of multiple-choice/open questions was administered via Qualtrics from November 2021 to February 2022, encompassing: (i) structure of care, (ii) investigations, (iii) treatments, (iv)counselling/supportive care and (v) outcomes. Clinical leads for pregnancy loss and fertility and clinical nurse/midwife specialists within each unit/clinic were invited to participate. The response rate 73% (24/33), varied by provider: Public RM care (18/19; 95%), 2/5 public fertility (40%); private fertility (3/9; 33%). Access to fertility expertise was limited in public RM clinics (39%). While investigations and treatments provided mostly adhered to guidelines, there was uncertainty regarding immunotherapies. Educational needs identified included fertility counselling, informative and supportive care resources. Clinical outcomes were seldom audited (2/22; 9%). Greater engagement with the private sector is required to unify care across sectors and to ensure standardised evidence-based care. Audit and outcomes reporting should be mandated. Lived experience of current care structures should inform service improvements.Impact Statement What is already known on this subject? There is a paucity of research into the appropriate clinical care of women/couples with infertility experiencing recurrent miscarriage, with a resulting deficit within international RM guidelines. It is known that RM care is variable and often not in line with guidance. What do the results of this study add? This study demonstrates that while care is largely in line with clinical practice guidelines, there is variation in counselling, imaging and surgical treatments offered. Areas for education identified included fertility counselling and resources for information provision and supportive care. Clinical outcomes were seldom audited. What are the implications of these findings for clinical practice and/or further research? Fertility care must expand to ensure access for women with RM and infertility. Further research exploring barriers and facilitators to the delivery of evidence-based care for women/couples with infertility and RM is required. The lived experiences of service users must inform service improvements.